2008
DOI: 10.1016/j.survophthal.2008.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Tools for Glaucoma Detection and Management

Abstract: Early diagnosis of glaucoma is critical to prevent permanent structural damage and irreversible vision loss. Detection of glaucoma typically relies on examination of structural damage to the optic nerve combined with measurements of visual function. To aid the clinician in evaluation of visual function and structure, computer-based devices such as confocal scanning laser ophthalmoscopy, scanning laser polarimetry, and optical coherence tomography provide quantitative assessments of structural damage, and visua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
108
0
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(116 citation statements)
references
References 137 publications
(167 reference statements)
2
108
0
6
Order By: Relevance
“…Where GCc equals the calculated number of GC within the visual field stimulus, GCL T represents the GCL thickness in microns, and GC D represents the ganglion cell density per mm 3 of GCL tissue. The analysis grid was spatially matched to the 68 stimulus locations of the 10-2 visual field test grid (white dots) and four points of the 30-2 visual field test grid at 12.78 eccentricity (pink dots), taking lateral ganglion cell displacement into account.…”
Section: Ganglion Cell Count Estimatementioning
confidence: 99%
See 1 more Smart Citation
“…Where GCc equals the calculated number of GC within the visual field stimulus, GCL T represents the GCL thickness in microns, and GC D represents the ganglion cell density per mm 3 of GCL tissue. The analysis grid was spatially matched to the 68 stimulus locations of the 10-2 visual field test grid (white dots) and four points of the 30-2 visual field test grid at 12.78 eccentricity (pink dots), taking lateral ganglion cell displacement into account.…”
Section: Ganglion Cell Count Estimatementioning
confidence: 99%
“…2 The associated functional loss mirrors the spatial pattern of the structural loss on psychophysical assessments such as visual field testing, and the concordance between structural and functional loss is considered diagnostic of glaucoma. 3,4 However, discordance between structural and functional aspects is commonly observed 5,6 and may hinder the early clinical detection of glaucoma. 7,8 Hence, the relationship between GC population (structure) and visual sensitivity (function) in glaucoma has been an ongoing topic of investigation.…”
mentioning
confidence: 99%
“…7,8 Optical coherence tomography (OCT) is a high-resolution, noninvasive imaging technique that uses near infrared light to produce images used to generate quantitative measurements of the RNFL. [9][10][11] Studies have demonstrated that RNFL thickness correlates with disease subtype, visual acuity, disability status, disease activity, and MRI measures of optic nerve atrophy in MS. 4,[12][13][14][15][16][17] As such, use of OCT as an endpoint in clinical trials of neuroprotective drugs and as a structural marker for disease activity has been suggested. 15,18 However, OCT use in everyday clinical management of patients with MS has not been well-elucidated.…”
mentioning
confidence: 99%
“…Overall, these structural parameters of the optic nerve head are well established in the medical community and verified in several studies (Greaney et al, 2002;Sharma et al, 2008). As these parameters are derived from structural measurements to characterize structural glaucomatous changes they are very meaningful and intuitive to the physician.…”
Section: Introductionmentioning
confidence: 75%